Stumpage Appraisal Using Tender Price in Pahang, Peninsular Malaysia - Zamah Shari, Nur Hajar (1999)
Previous studies have shown that tropical forests are under valued. This may result in unsustainable harvest, biased against conservation and low revenue to the government. A study was conducted m the state of Pahang, Peninsula Malaysia to determine the trend and patterns of tender prices based on 277 logging transactions between the period 1993 to 1998. An analysis was also conducted to compare the actual tender price offered by the concessionaires with the estimated tender price using residual value technique for three logging compartments. Data on tender prices were collected from the Pahang State Forestry Department sales record. For the comparative analysis of tender price between actual and estimated price, data were obtained from state-own logging enterprises. These include data on timber volume, log price, logging and actual tender price. The result indicate that the average tender price offered by the concessionaires is RM6,271.44 per hectare, and the highest average tender price IS RM14,236.51 per hectare. The highest average tender prices (RM10,558.76 per hectare) is in the District of Lipis, followed by District of Jerantut (RM8,996.21). In general, the tender price has shown fluctuating trends during the study period, mainly due to economic situation and demand supply situation of log. The result from comparative analysis indicates that the concessionaires are relatively over-estimate the stumpage value, ranging from 6.4 to 20.14 percent. The study suggests that tendering would indicate full market value of a logging compartment when it is used for timber production. The estimated tender price using the residual value technique can be used to set the floor price. Further research is needed to obtain a comprehensive tendering mechanism before Implementing any police reform on forest revenue system in the state.